High density planting system in ’Amrapali’ mango (Mangifera indica) - SINGH, SANJAY; YADAV, G S; SINGH, JAYANT; HODA, M N (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1997-99 to study the effect of different plant densities on growth, yield and fruit-quality characters of ’Amrapali’ mango (Mangifera indica L.) Five planting systems, viz (i) square system (1 600 plants/ha), (ii) hedge row system (2670 plants /ha), (iii) double hedgerow system (3 556 plants/ ha), (iv) paired planting (2 133 plants/ ha) and (v) cluster planting (2 844 plants/ha), were studied. Maximum yield/unit area was recorded in double hedge row planting system which was closely followed by cluster planting and hedge row system of planting. Double hedge row planting system can be adopted by mango growers for getting better productivity per unit area.